Preoperative nutritional scores to predict mortality after liver transplantation: a retrospective cohort study - Eun Jung Kim; Jin Ha Park; Soo Yeon Kim; Jin Sun Cho (Anesthesia and Pain Medicine)
Background Malnutrition is a well-known risk factor for mortality and morbidity. We investigated whether preoperative malnutrition, diagnosed using an objective nutritional index, was associated with postoperative mortality in patients undergoing liver transplantation (LT). Methods This retrospective cohort observational study assessed the preoperative nutritional status of 440 patients who underwent LT, using the Nutritional Risk Index (NRI), Prognostic Nutritional Index (PNI), and Controlling Nutritional Status (CONUT) score. We evaluated the association between preoperative malnutrition and 3-year postoperative mortality using the Kaplan–Meier curve and log-rank test. In addition, we identified prognostic factors for mortality using Cox proportional hazard analysis. Results Malnutrition was identified in 72.7% (n = 320), 66.1% (n = 291), and 97.3% (n = 428) of patients as assessed by the NRI, PNI, and CONUT score, respectively. The Kaplan–Meier survival curve demonstrated that mortality increased with the presence and severity of malnutrition risk, as assessed by the NRI and PNI, respectively; however, NRI was the only index identified as an independent risk factor for mortality, along with preoperative renal replacement therapy, platelet count, and C-reactive protein. After adjustment, lower NRI was associated with a higher risk of mortality (hazard ratio 0.97, 95% confidence interval 0.95–0.99, P = 0.009). The malnutrition group (NRI ≤ 100) had a significantly greater incidence of postoperative acute kidney injury than that of the normal group. Conclusions Preoperative NRI is an independent risk factor for mortality after LT, and therefore it would be a helpful tool for mortality risk stratification in patients undergoing LT.